706 BT7480, a fully synthetic tumor-targeted immune cell agonist (TICA™) induces tumor localized CD137 agonism and modulation of tumor immune microenvironment. (9th November 2020) - Upadhyaya, Punit; Hurov, Kristen; Kublin, Jessica; Ma, Jun; Repash, Elizabeth; Kleyman, Marianna; Kristensson, Julia; Kanakia, Drasti; You, Fanglei; Chen, Liuhong; Haines, Eric; Battula, Sailaja; et al.
Abstract : Background: After disappointing first clinical experiences with agonistic anti-CD137 (4-1BB) antibodies, a new generation of both systemic and targeted CD137 agonists is entering clinical development. 1–3 These strategies rely on biologic agents with suboptimal properties for CD137 agonism due to their relatively large sizes and long circulating half-lives. These properties may limit their tissue penetration and cause sustained agonism resulting in overstimulation and activation-induced cell death of lymphocytes due to continuous exposure.Fully synthetic constrained bicyclic peptides (Bicycles™) with antibody-like affinities and target selectivity are uniquely suited to circumvent the above barriers to optimal targeted CD137 agonistic therapeutics. BT7480 is a tumor-targeted immune cell agonist (TICA) designed to deliver a highly potent CD137 agonist to Nectin-4 overexpressing tumor tissue with a flexible dosing schedule maximizing anti-tumor activity while circumventing the need for continuous systemic exposure. Methods: BT7480 functional activity in vitro was analyzed by measuring IL-2 and IFN gamma production from primary human PBMC/tumor cell co-cultures. BT7480 in vivo activity was determined in huCD137-syngeneic tumor models using tumor immune cell and transcriptional profiling by FACS, IHC, and Nanostring as well as tumor growth kinetics as read-outs. Results: BT7480 binds potently and simultaneously to Nectin-4 and CD137 as assessed biochemically and caused Nectin-4-dependent CD137 agonism in primary human PBMC co-cultured with tumor cells. Treatment of Nectin-4 expressing tumors in immunocompetent mice with BT7480 leads to profound reprogramming of the tumor immune microenvironment including increased T cell infiltration and upregulation of a cytotoxic cell gene signature. BT7480 treatment induces complete tumor regressions and subsequent resistance to tumor re-challenge. TICA-dependent anti-tumor activity and established immunologic memory are dependent on cytotoxic T cells. Importantly, BT7480 in vivo activity is not dependent on continuous plasma exposure since once weekly dosing of BT7480 provides a maximum anti-tumor activity despite minimal BT7480 plasma exposure after day 2.BT7480 demonstrates linear pharmacokinetics in non-human primates and appears well tolerated at exposures in excess of the predicted efficacious exposure in humans. Conclusions: BT7480 is a highly potent Nectin-4 expression dependent CD137 agonist with optimal target binding, pharmacologic, and pharmacokinetic properties that enable intermittent dosing for curative effect through modulation of tumor immune microenvironment in syngeneic mouse tumor models. BT7480 is currently being evaluated in IND-enabling safety studies. Ethics Approval: The care and use of animals were reviewed and approved by the Institutional Animal Care and Use Committee (IACUC) of WuXi AppTec and conducted in accordance with the regulations of the Association for Assessment and Accreditation of Laboratory Animal Care (AAALAC). References: Hinner, et al. Tumor-localized costimulatory t-cell engagement by the 4-1BB/HER2 Bispecific antibody-anticalin fusion PRS-343. Clin. Cancer Res 2019 Oct 1;25(19):5878–5889. Claus, et al. Tumor-targeted 4-1BB agonists for combination with T cell bispecific antibodies as off-the-shelf therapy. Sci. Transl. Med 2019 Jun 12;11(496):eaav5989. Eskiocak, et al. Differentiated agonistic antibody targeting CD137 eradicates large tumors without hepatotoxicity. JCI Insight 2020 Mar 12;5(5):e133647.